Participatory Research With Children: From Child-Rights Based Principles to Practical Guidelines for Meaningful and Ethical Participation - Amanda Angelöw; Elia Psouni (International Journal of Qualitative Methods)
While the Convention on the Rights of the Child (UNCRC) does not address research, it instigated a recognition that decisions concerning children and youth must be based on knowledge of their experiences from their own perspective and consider their specific views and wishes, highlighting their right to be heard. Participatory research underscores this right, arguing the engagement of children and youth throughout the research process. Studies indicate positive socioemotional and cognitive outcomes for youth co-researchers. It is reasonable to also expect gains in terms of research relevance and quality. However, guidelines are urgently needed, to help establish reproducible research practices and align with child-rights based processes. Based on UNCRC principles for ethical and meaningful child participation, we thus conceptualize practical guidelines for participatory research with children and youth, which we illustrate with concrete practices how children/youth can be included as co-researchers in processes that are safe, empowering, and relevant.